2018
DOI: 10.1002/jeab.478
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate assessment of the rapidly changing procedure with McDowell's Evolutionary Theory of Behavior Dynamics

Abstract: A multivariate analysis is concerned with more than one dependent variable simultaneously. Models that generate event records have a privileged status in a multivariate analysis. From a model that generates event records, we may compute predictions for any dependent variable associated with those event records. However, because of the generality that is afforded to us by these kinds of models, we must carefully consider the selection of dependent variables. Thus, we present a conditional compromise heuristic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Popa and McDowell (2016) studied the effect of wide ranges of mutation rates and reinforcer magnitudes, and a larger phenotype range and therefore longer bit-string (i.e., genotype) length. Li et al (2018) experimented with smaller target class sizes. This work on the boundaries of the theory has not called into question the standard settings used in the present, or in any previous, research.…”
Section: The Evolutionary Theory Of Behavior Dynamicsmentioning
confidence: 99%
“…Popa and McDowell (2016) studied the effect of wide ranges of mutation rates and reinforcer magnitudes, and a larger phenotype range and therefore longer bit-string (i.e., genotype) length. Li et al (2018) experimented with smaller target class sizes. This work on the boundaries of the theory has not called into question the standard settings used in the present, or in any previous, research.…”
Section: The Evolutionary Theory Of Behavior Dynamicsmentioning
confidence: 99%
“…Li, Hautus, and Elliffe () described a novel method of fitting computational theories to data from individual organisms. Li, Elliffe, and Hautus (in press) used a version of this method to fit the ETBD to data from Davison and Baum's () experiment (just described), in which rapidly changing within‐session reinforcer ratios were arranged. They concluded that the theory accounted relatively well for the distribution of responding between operanda in individual birds.…”
Section: Evidence Supporting the Evolutionary Theorymentioning
confidence: 99%
“…They concluded that the theory accounted relatively well for the distribution of responding between operanda in individual birds. Important questions have been raised about this method and the interpretation of its results (e.g., Li, Elliffe, and Hautus, in press; McDowell & Klapes, ), but if these questions can be answered satisfactorily, then Li et al's method will be a useful addition to the tools used to evaluate computational theories.…”
Section: Evidence Supporting the Evolutionary Theorymentioning
confidence: 99%
“…Although the conceptual framework of selection by consequences has a long tradition in behavior analysis and remains a popular narrative (e.g., Baum, 2023; Becker, 2019; Donahoe, 2011; Donahoe et al, 1993; Hull et al, 2001; McDowell, 2013, 2023; Simon, 2020; Simon & Hessen, 2019), it seems to have had few effects on the actual practices of many behavior analysts (but see McDowell, 2019, and Li et al, 2018). One possible reason for this gap between theory and practice may be that operant selection is sometimes used as a mere synonym for what is traditionally called “reinforcement.” Of course, adopting the language and vocabulary of evolutionary biology alone does not add much to the theoretical foundations of the experimental analysis of behavior.…”
Section: Introductionmentioning
confidence: 99%